(untitled) (Padmakanya Journal of Science and Technology, 2025)
Traffic noise pollution has emerged as a growing environmental and public health concern in urban areas, particularly affecting personnel with continuous roadside exposure. Traffic police being directly exposed to prolonged roadside noise, possess significant health risks. Despite the risks, limited research has been conducted in this region in assessment of health effect from noise. This study aimed to assess the environmental noise level at eight major traffic junctions along the Butwal Bhairahawa highway in the Rupandehi District and examined associated health impacts on traffic police officers in comparison to local residents. Maximum noise levels ranged from 77.2 to 102.6 dB(A) in the morning (9:00–10:00 AM) and 78.4 to 100.8 dB(A) in the afternoon (1:00–2:00 PM). Yogikuti Chowk recorded the highest morning noise, with an average Leq of 85.32 dB(A). Minimum noise levels ranged from 56.8 to 65.8 dB(A) in the morning and 51.9 to 65.2 dB(A) in the afternoon. Traffic police consistently reported higher rates of health problems across nearly all categories, reflecting their greater exposure to traffic noise compared to local residents. The Chi-square test revealed a statistically significant association between noise exposure and several health problems among traffic police officers specifically, hearing difficulties (χ² = 7.276, p = 0.007), tinnitus (χ² = 4.917, p = 0.027) and fatigue (χ² = 19.728, p < 0.001). In addition, none of the surveyed traffic police officers reported using any form of personal protective equipment (PPE) which highlights a serious gap in occupational safety. This outlines the need of improved traffic management strategies, strict enforcement of noise regulations and increased public awareness to better safeguard the health of both traffic police and public.